PENGEMBANGAN CANTING ELEKTRIK âCANTRIKâ YANG ERGONOMIS - , SITI LESTARININGSIH, Ir. Rini Dharmastiti, M.Sc, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Batik is a work of art for fashion, which is one of Indonesia's cultural riches which have developed. Especially for batik tulis, it has been recognized by UNESCO as a cultural heritage. The use of traditional Canting is difficult and if the user do not careful it will be dangerous. Based on this background, Balai Besar Kerajinan dan Batik (BBKB) conducted a research for developing an electronic canting (Cantrik). The purpose of this research is to develop a more ergonomic Cantrik which is purposed for making the canting process easier and everyone can do this process, because due to the ergonomic suitability of tools, methods, and the working environment of the human condition can be pursued so that humans can work optimally. For developing the more ergonomic Cantrik, Kano method and QFD will be used. The Kano method is used to determine the attributes that will be developed in the Quality Function Deployment (QFD). This step is purposed for making the products design based on consumer needs, in order to develop the Cantrik lama. This research used 40 persons as respondents. After that, a prototype will be made and gap analysis will be done in this research. The Cantrik baru, can fit the user needs and it is more ergonomic (easy, flexible, safe, convenient and compliance measures) than before when it is used in the canting process based on 10 product quality attributes which was mapped in the House of Quality from 17 customer product quality attributes, as well as the evaluation results demonstrate the value of a positive gap (expectations of respondents increased) with an attribute that gets priority for development is product quality attributes "Can be used with pedestal or not" and the product quality attributes "Design tools according to hand anthropometry".